INTERPERSONAL METADISCOURSE MARKERS IN JACINDA ARDERN SPEECH AT CHRISTCHURCH MEMORIAL - Desma Putri Azijah; Ingatan Gulö (Linguistics and Literature Students' Journal, 2020)
The research aims to find the types of interactive and interactional metadiscourse markers in Jacinda Ardern’s speech at Christchurch memorial, and the function of each metadiscourse markers found in the speech. In doing the analysis, the writers applied Hyland’s (2005) framework of interpersonal metadiscourse. This research applied descriptive qualitative method in analyzing and presenting the results. The findings show that Jacinda Ardern used both interactive and interactional resources of interpersonal metadiscourse. She used the interpersonal metadiscourse markers based on its functions. By the use of metadiscourse markers in the speech, Jacainda Ardern has successfully delivered a well-organized and persuasive speech, and built a good relationship with her audience.